Effect of Fungicide Applications on Grain Sorghum (Sorghum bicolor L.) Growth and Yield. (21st February 2017) - Fromme, Dan D.; Price, Trey; Lofton, Josh; Isakeit, Tom; Schnell, Ronnie; Dodla, Syam; Stephenson, Daniel; Grichar, W. James; Shannon, Keith
Abstract : Field studies were conducted in the upper Texas Gulf Coast and in central Louisiana during the 2013 through 2015 growing seasons to evaluate the effects of fungicides on grain sorghum growth and development when disease pressure was low or nonexistent. Azoxystrobin and flutriafol at 1.0 L/ha and pyraclostrobin at 0.78 L/ha were applied to the plants of two grain sorghum hybrids (DKS 54-00, DKS 53-67) at 25% bloom and compared with the nontreated check for leaf chlorophyll content, leaf temperature, and plant lodging during the growing season as well as grain mold, test weight, yield, and nitrogen and protein content of the harvested grain. The application of a fungicide had no effect on any of the variables tested with grain sorghum hybrid responses noted. DKS 53-67 produced higher yield, greater test weight, higher percent protein, and N than DKS 54-00. Results of this study indicate that the application of a fungicide when little or no disease is present does not promote overall plant health or increase yield.